Jadaliyyah Dilâliyyah haula al-Ta'bîrât al-Ishthilâhiyyah wa Ta'addud al-Ma'na fî Insyâi al-Thalabah al-Mustawa al-Madrasiy wa al-Mustawa al-Jâmi'iy (Dirâsah Tahlîliyyah Naqîdiyyah fî al-Tadakhkhul al-Dilâliy) - Uyun Thayyibah; Nurdiana Arifah (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2024)
Interference in insya' writing skills should be considered a very unnatural phenomenon. The reason is that the writing process requires structure in composing words, as well as careful consideration of every expression to be conveyed. In contrast to maharah kalam which is spontaneous, where expressions are thrown out without in-depth planning. Meanwhile, interference in semantic aspects is rarely the focus of attention as is generally the case with errors in syntax and morphology. Errors in these two aspects often get more attention than the attention given to interference in the semantic domain. Therefore, this study aims to critically analyze semantic interference around idioms and meaning relations that occur in the insya' of school and university level learners. The research method used is descriptive qualitative research method by conducting text content analysis. The results of the text content analysis show that semantic interference around idioms occurs in the use of the letter jar while interference around meaning relations occurs in the choice of synonyms and ambiguity of meaning. The implication of this study is the importance of a deep understanding of the semantic differences between Arabic and Indonesian. This can help language teaching and learning as well as improve the understanding and interpretation of insya' texts that contain interference.